Effectivnes Active Cycle of Breathing Technique Therapy on Dyspnea in Pulmonary Tuberculosis Patients at Tangerang Hospital - Subiakto, Toto; Nasihin, Nasihin; Dalami, Ermawati; Natasya, Ester (Journal of Smart Nursing and Health Science, 2023)
Background: Pulmonary tuberculosis (TB) is one of the leading causes of death worldwide. Indonesia ranks 2nd (14%) in the highest number of Pulmonary TB cases in the world. Banten Province (64%) ranks first with the highest number in Indonesia. Problems caused by Pulmonary TB will interfere with the respiratory tract, such as chronic coughing and shortness of breath. 85% of people with Pulmonary TB were successfully treated within 6 months by routinely conducting pharmacological therapy and non-pharmacological therapy to treat the side effects of infections that occurred. Purpose this study was conducted to determine the effect of the active cycle of breathing technique therapy on the shortness of breath in pulmonary TB patients in Tangerang regency hospital. Method: This study is a quasy experiment with a one-group pretest-posttest design approach. The samples in this study were Pulmonary TB patients who experienced shortness of breath due to sputum retention, which totaled 16 respondents. Purposive sampling technique with 1 intervention group. This group will be given ACBT therapy as much as 2x / day for 5 days. Results: The results showed differences in the scale of shortness of breath before and after the administration of Active Cycle Of Breathing Technique (ACBT) therapy against shortness of breath of Pulmonary Tuberculosis sufferers with a P-Value of 0.000<0.05. The statistical results showed a decrease in the tightness scale by 2.44 points. conclusion: the active cycle of breathing technique therapy reduces shortness of breath in pulmonary TB patients.